Effects of micronutrients on the vegetative growth and shoot nutrient status of chickpea (Cicer arietinum L.) grown under drought stress condition (Dhaka University Journal of Biological Sciences, 2025)
This study evaluated the effects of micronutrients (B, Fe and Zn) on the vegetative growth and shoot nutrients (K, Ca, Fe and Zn) status of chickpea (Cicer arietinum L.) grown under different moisture regimes (50%, Well-Watered; 25%, Mild-Stressed and 12.5%, Severe-Stressed) in greenhouse condition. Micronutrients were supplied alone and in combination as foliar spray to plants with severe-stressed condition. Results showed a significant decline in shoot height (p < 0.0001), fresh weight (p < 0.0001), dry weight (p < 0.0001) and relative water content (p = 0.0001) from well-watered to severe-stressed condition, although no remarkable change was observed after the application of micronutrients. Significant reduction in root fresh weight (p=